The Opinions of a Group of Law Students Regarding the Process of Justice Making – As a Supreme Value of the Judicial System - IOVAN, Marțian (Journal of Legal Studies, 2014)
Based on a sociological research, the author of this article aims to identify the beliefs and the attitudes of a group of BA and MA students enrolled in university programs of Juridical Science, regarding their apprehension of the principles of justice - as the central value of the Romanian judicial system. This would contribute to the implementation of justice in the actual Romanian economic, political, and judicial structure. The data analysis provides the necessary information for comprehending the extensions of justice and injustice within the specific social context. A real distance between reality and the political doctrines, and the classical and post-modern philosophical theories of justice as well can be noticed. The resulting conclusions could provide solid settings in order to develop a number of strategies / public policies to shape a more honest society.